Imbalanced media portrayal: a content analysis of precision medicine in US news of 2015–2021 - Peng, Wei; Seo, Hae Yeon; Choi, Juwhan; Jia, Xiaofeng (Frontiers in Communication, 2024)
Introduction: Engaging diverse participants is vital to precision medicine (PM) but has been limited by low knowledge and concerns about various issues related to PM research. News media is an important channel of information that can shape public understanding and perception of PM. However, how PM is represented in news media has not been sufficiently understood. Method: The study used quantitative content analysis to evaluate the portrayal of PM in US print news media between 2015 and 2021 (N = 198). Three domains of factors related to PM portrayed in news articles were coded: 1) characteristics of PM, 2) target diseases of PM and their related characteristics, and 3) non-scientific news frames. Result: There was considerable news coverage of the treatment benefits of PM, especially for cancer. Potential risks or concerns, non-cancer diseases, and non-treatment issues that could be important to diverse populations were less covered. News articles frequently cited scientists, patients, and government officials with different focuses on PM. Discussion: The study highlighted the need for accurate and complete information about PM in news media for diverse participants. News media should actively explore social, ethical, and legal issues to support the engagement of diverse populations.